Impact of COVID-19 on Stroke Admissions and the Medical Care System in the Tokyo Metropolitan Area - Ota, Takahiro; Shiokawa, Yoshiaki; Hirano, Teruyuki (Frontiers in Neurology, 2020)
Aims: This study aimed to assess the number of patients with acute stroke seeking medical emergency care since the declaration of the state of emergency in the COVID-19 pandemic in the Tokyo metropolitan area of Japan. Methods: In this combined retrospective and prospective multicenter survey, data on the numbers of hospital admissions due to acute ischemic stroke, of large vessel occlusion (LVO) cases, and of reperfusion therapies performed from February to July 2020, restrictions of the medical care system, and comprehensive stroke center (CSC) scale scores were collected in 19 stroke centers in Tokyo. Results: In the survey period, 3,456 patients were admitted with acute stroke. There was a decrease in the number of admissions (-22%), LVO (-22%), thrombolysis (-6%), and thrombectomy (-23%) during the state of emergency, but the ratio of thrombectomy to LVO cases was not different. The acceptance of acute stroke cases by emergency transport and emergent operations in the central eastern area of Tokyo, was also significantly decreased to less than 50% and remains less than 60%. According to CSC scores, each hospital restricted their infrastructure or educational activities according to their medical resources. There was only one stroke case with COVID-19 (thrombectomy case) in all 3,456 patients in this study. Conclusion: The COVID-19 pandemic had a major impact on stroke care in Tokyo, including stroke admissions and medical care systems, resulting in a significant reduction in thrombolysis and thrombectomy. The extent of the drop may be the result of the number of COVID-19 patients.